Chronic Inflammation as a Potential Predictive Factor of Nivolumab Therapy in Non-small Cell Lung Cancer - Svaton, Martin; Zemanova, Milada; Skrickova, Jana; Jakubikova, Lenka; Kolek, Vitezslav; Kultan, Juraj; Koubkova, Leona; Bejckova, Alzbeta; Salajka, Frantisek; Hrnciarik, Michal; Melichar, Bohuslav; Vrana, David; et al. (Anticancer research, 2018)
AIM: To investigate potential associations between clinical and standard peripheral blood biomarkers and clinical outcome in patients with non-small cell lung cancer (NSCLC) treated with nivolumab. PATIENTS AND METHODS: A total of 120 patients with advanced NSCLC treated at seven comprehensive cancer care centers were analyzed in this national retrospective study. Survival statistics were evaluated using the Kaplan-Meier method and Cox analysis. RESULTS: Among clinical parameters, histology was significantly associated with progression-free survival. Univariate Cox-proportional hazards model indicated prognostic and predictive role of a panel of laboratory parameters reflecting chronic inflammatory pattern (elevated neutrophil count, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, C-reactive protein and decrease in hemoglobin and albumin). Higher serum calcium concentration was also associated with nivolumab treatment effect. CONCLUSION: Tumor histology was the only clinical parameter predicting the outcome of nivolumab treatment. Among the laboratory parameters, our analysis identified a laboratory panel reflecting chronic inflammation as a potential predictive marker of nivolumab treatment.
Keywords: senioři; analýza přežití; Inflammation; Retrospective Studies; Survival Analysis; Prognosis; Chronic Disease; chronická nemoc; zánět; Middle Aged; mužské pohlaví; nádory plic; Adult; Nivolumab; nemalobuněčný karcinom plic; ženské pohlaví; prognóza; retrospektivní studie; Humans; Carcinoma, Non-Small-Cell Lung; lidé středního věku; rizikové faktory; dospělí; Female; Aged; Risk Factors; Lung Neoplasms; lidé; Male; nivolumab